Gill monogeneans of the chub mackerel, Scomber japonicus from Madeiran waters of the Atlantic Ocean, Portugal - Costa, G. (2007)
Five species of monogeneans were recovered from the gill filaments of 181 chub mackerel, Scomber japonicus, from the Madeiran waters of the Atlantic Ocean, Portugal, during 2004/2005. The monogenean Pseudokuhnia minor showed the highest prevalence (98.68%) and a mean intensity of 28.23, followed by Kuhnia scombri (prevalence of 43.71% and mean intensity of 2.69) and K. scombercolias (prevalence of 39.1% and a mean intensity of 1.81). Kuhnia sprostonae and Grubea cochlear were rare, occurring in only one and five fish hosts respectively. No correlation between fish host length and mean intensity of infection with the three most abundant monogeneans was found. However, significant differences in prevalence and abundance were found in relation to date of sampling for P. minor, and all parasites were aggregated in their distribution.